RADIATION DOSE EVALUATION IN THORAX RADIOGRAPHY EXAMINATION EVALUASI DOSIS RADIASI PADA PEMERIKSAAN RADIOGRAFI THORAX - ARSYA DESTIAN RAHMADHAN (Wealth Community Empowerment, 2025)
ABSTRACTThe radiation dose received by patients during Thorax examination can vary from one hospital to another. For this reason, the Indonesian government through BAPETEN has set the Indonesian Diagnostic Reference Levels in 2021 as a reference for radiation doses in medical imaging. This study aims to determine whether there is a comparison of these doses with the IDRL 2021 reference. This study is a quantitative study with an experimental and survey approach conducted at Tlogorejo Hospital, Semarang. The radiation dose value in the form of Entrance Surface Air Kerma (ESAK) was collected at Tlogorejo Hospital, Semarang. The ESAK value was obtained through simulation or measurement using a digital dosimeter placed on the surface of the water phantom for Thorax examination. The examination parameters used are standard parameters for adult Thorax examination in patients weighing 50-70 kg. Overall, 87 ESAK values were collected from Tlogorejo Hospital, Semarang. The results showed significant variations in the radiation dose of Thorax examination in hospitals with an average dose of 0.145 mGy. While the median ESAK value is 0.095 mGy. However, the study showed that the median ESAK value of Thorax examination at the hospital where the study was conducted was still within the IDRL 2021 recommendation limit, which was below 0.4 mGy. This study shows the importance of continuous optimization efforts to ensure radiation safety in patients undergoing diagnostic radiology examinations.